Bone aluminum measured in miners exposed to McIntyre powder. Issue 6 (3rd June 2022) - Bickley, L. M.; Martell, J.; Cowan, D.; Wilken, D.; Yan, W.; McNeill, F. E.; Zarnke, A.; Hedges, K.; Chettle, D. R.
Abstract: A small pilot study was conducted to test whether the technique of in vivo neutron activation analysis could measure bone aluminum levels in 15 miners who had been exposed to McIntyre Powder over 40 years prior. All miners were over 60 years of age, had worked in mines that used McIntyre Powder, and were sufficiently healthy to travel from northern to southern Ontario for the measurements. Individual aluminum levels were found to be significantly greater than zero with 95% confidence ( p  < 0.05) in 7 out of the 15 miners. The inverse variance weighted mean of the 15 participants was 21.77 ± 2.27µgAl/gCa. This was significantly higher ( p  < 0.001) than in a group of 15 non-occupationally exposed subjects of a comparable age from Southern Ontario who had been measured in a previous study. The inverse variance weighted mean bone aluminum content in the non-occupationally exposed group was 3.51 ± 0.85µgAl/gCa. Since the use of McIntyre Powder ceased in 1979, these subjects had not been exposed for more than 40 years. Calculations of potential levels at the cessation of exposure in the 1970s, using a biological half-life of aluminum in bone of 10 to 20 years predicted levels of bone aluminum comparable with studies performed in dialysis patients in the 1970s and 1980s. This pilot study has shown that the neutron activation analysis technique can determine differences in bone aluminum between McIntyre Powder exposed and non-exposed populations even though 40 years have passed since exposure ceased. The technique has potential application as a biomarker of exposure in cross-sectional studies of the health consequences of exposure to McIntyre Powder.